Political determinants of privatizations in China: A natural experiment based on politician career concerns - Huang, Zhangkai; Liu, Jinyu; Ma, Guangrong; Xu, Lixin Colin (Journal of Corporate Finance, 2024)
We study the political determinants of the world's largest privatization program by exploiting an age-related discontinuity of politician promotion in China. As a local politician's age exceeds 58, his promotion likelihood quickly diminishes. Consistent with changes in the politician's incentives, we find that Chinese cities whose top officials were older than age 58 were less likely to privatize local state-owned enterprises. Using the promotion discontinuity as an instrument, we report that privatization has significant effects on the firm's efficiency.